Dendritic cells activated by cimetidine induce Th1/Th17 polarization in vitro and in vivo. (September 2022) - Qu, Yaqian; Bao, Lei; Zhao, Youliang; Li, Yiping; Ding, Mingcui; Hao, Changfu; Yao, Wu
Abstract: Dendritic cells (DCs) are powerful antigen presentation cells and the initiator of adaptive immune response. Cimetidine, a widely used drug for gastric ulcers treatment, has significant immunomodulatory ability. However, the effects of cimetidine on DC-mediated T cell activation need to be further explored. In this study, we constructed the in vitro and in vivo model of cimetidine exposure, and our data showed that cimetidine stimulated the maturity of immature DCs, and further enhanced its T cell priming capacity. In vivo, the number of rat splenic CD103 + DC were not altered after cimetidine exposure, but the expression of surface markers CD54, CD11c, and MHC-II of which were up-regulated. Importantly, cimetidine interfered with DC-mediated T cell polarization, which was reflected in the up-regulation of Th1 and Th17 cells and the down-regulation of Th2 and Treg cells in vitro and in vivo . These results indicate that cimetidine can induce DC activation and promote DC mediated pro-inflammatory T cell response while weaken immunosuppressive T cell response. Highlights: Cimetidine could activate dendritic cells (DCs) in vitro and in vivo . Cimetidine treatment cause phenotypical and functional changes of immature DCs. Cimetidine exposure affect DC-mediated T cell activation and polarization.